Features of ‘New’ Students and the Potential of Future Teachers: First Effects of “The Unteachables” International Project - Kulpa-Puczyńska, Aleksandra (Cardinal Stefan Wyszynski University in Warsaw, 2020)
The problem of students with difficulties in functioning in a school environment is nowadays becoming significant, as the environment often does not respond to unique and complex needs of young learners, such as modern ways of exchanging experience and knowledge, or the possibility of active participation in the community of learners and support networks. This state of affairs dictates the need to create new educational resources (also developed on the basis of cooperation of the academic community with secondary school teachers, or the cooperation of experts and practitioners from various countries) for future teachers who may face, for example, the problem of “burnt-out” young students. The main purpose of this paper is to share the first research results and reflections concerning the implementation of “The Unteachables” Erasmus+ project at the Faculty of Education and the Faculty of Biology and Environmental Sciences at the Cardinal Stefan Wyszynski University in Warsaw (in cooperation with partners from Denmark – project coordinator, Iceland, Spain, Slovenia and Italy). Znaczący staje się dzisiaj problem uczniów z trudnościami w funkcjonowaniu w środowisku szkolnym, które często nie odpowiada na unikalne i złożone potrzeby młodych osób uczących się, dotyczące np. nowoczesnych sposobów wymiany doświadczeń oraz wiedzy czy możliwości aktywnego uczestnictwa we wspólnocie uczących się i sieci wsparcia. Oznacza to m.in. konieczność tworzenia nowych zasobów edukacyjnych (powstałych także na bazie współpracy środowiska akademickiego z nauczycielami szkół średnich, kooperacji ekspertów i praktyków z różnych krajów) dla przyszłych nauczycieli, którzy będą musieli stawić czoła np. problemowi „wypalonych” uczniów. Głównym celem tekstu jest podzielenie się pierwszymi wynikami badań oraz refleksjami związanymi z realizacją na Wydziale Nauk Pedagogicznych oraz Wydziale Biologii i Nauk o ŚrodowiskuUniwersytetu Kardynała Stefana Wyszyńskiego w Warszawie (we współpracy z partnerami z Danii – koordynator projektu, Islandii, ...